Couples, Careers, and Spatial Mobility - Lea Nassal; Marie Paul (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
We investigate the effects of long-distance moves of married couples on both spouses' earnings, employment and job characteristics based on a new administrative dataset from Germany. Employing difference-in-difference propensity score matching and accounting for spouses' pre-move employment biographies, we show that men's earnings increase significantly after the move, whereas women suffer large losses in the first years. Men's earnings increases are mainly driven by increasing wages and switches to slightly larger and better paying firms. Investigating effect heterogeneity with respect to pre-move relative earnings or for whose job opportunity couples move, confirms strong gender asymmetries in gains to moving.
Keywords: J61; J16; R23; 330; Long-distance moves; labour market careers; gender gap